Congenital Extrahepatic Portosystemic Shunt (Abernethy Malformation Type Ib) With Associated Hepatocellular Carcinoma: Case Report and Literature Review. (July 2017) - Benedict, Mark; Rodriguez-Davalos, Manuel; Emre, Sukru; Walther, Zenta; Morotti, Raffaella
Abernethy malformation, also termed congenital portosystemic shunt and congenital absence of portal vein is the result of malformation of the splanchnic venous system. Congenital portosystemic shunts are divided into extra- and intrahepatic shunts. Two shunts have been defined: Type I is characterized by the complete diversion of portal blood into the vena cava with an associated congenital absence of the portal vein. Type II is defined by an intact but diverted portal vein through a side-to-side, extrahepatic connection to the vena cava. The clinical manifestations of Abernethy malformation are diverse with a typical presentation consisting of hypoxia and hepto-pulmonary syndrome. Histologically, focal nodular hyperplasia, nodular regenerative hyperplasia, liver adenoma, hepatoblastoma, and hepatocellular carcinoma have all been reported. Herein, we report a case of Abernethy malformation, type Ib, in a 12-month-old male who was found to have a small hepatocellular carcinoma at the time of explant. The immunohistochemical characteristics in relation to the genetic aspects are discussed. To our knowledge, this is the first reported case of hepatocellular carcinoma developing in a patient who is under the age of 5 years with Abernethy malformation.